Unequal access to The Global Financial Safety Net: An index for the quality of crisis finance - Marina Zucker Marques; Laurissa Mühlich; Barbara Fritz (Freie Universität Berlin, School of Business & Economics, 2023)
The Global Financial Safety Net (GFSN) - the institutions and arrangements that provide short-term crisis finance - has turned into a highly complex, uncoordinated system of global, multilateral, and bilateral instruments. The present paper elaborates on a composite index of the GFSN to analyse its preparedness for shielding countries from financial crises. This first-of-its-kind index comprises six components that measure the vulnerability and resilience of individual countries to financial crises derived from economic and political economy financial crisis literature. We apply this index to data from 192 UN member countries we collected in the GFSN tracker for the period of the COVID-19 pandemic in terms of their asses to and use of the GFSN. This index, and the use of novel forms of graphical displaying, allow us to identify a hierarchy in the access to short-term liquidity by the GFSN. At the bottom, we find low-income countries with sole access to IMF standard conditional crisis finance, while we find at the top countries with access to bilateral currency swaps, especially those provided by the US Federal Reserve. Our analysis also reveals that first, the temporary reformed unconditional access of IMF crisis finance during the pandemic has temporarily improved those countries' position in the GFSN hierarchy; second, bilateral swaps as crisis finance instruments reinforce the GFSN hierarchy. Since access to adequate emergency liquidity is decisive for a country's financial crisis prevention capacity and the ability to engage in social cohesion and climate policy, we suggest to flatten the hierarchy by keeping access to IMF unconditional finance open beyond the COVID-19 crisis, expanding regional financial arrangements, and by coordinating GFSN elements, including currency swap providing central banks.
urn:nbn:de:kobv:188-refubium-38600-2
Keywords: 330; Global financial safety net; financial crisis; short-term crisis finance; IMF; central bank policies; regional financial arrangements